Cause-related marketing: it's influence on consumers' choice of hypermarket - Wong, Foong Yee; Ng, Siew Imm; Lim, Chin Hwa (Universiti Malaysia Sarawak, 2018)
Malaysia has undergone market changes which lead to transformation from small shops to larger scale shops due to the globalization. The larger scale shop such as hypermarkets will increase the supply from local suppliers if the demand of consumers toward local product is high. This indicates that cause-related marketing concept can be applied if consumers are favour to hypermarkets that intend to support local product. Therefore, this study aims to examine the factors that influence consumers’ participation intention on “support local product” CRM campaign in the Malaysia context. There were six variables included to determine their effects on participation intention in “support local product” campaign which were firm motive, perceived corporate social responsibility, offer elaboration, brand attitude, ethnocentrism and environmental concern. Multiple regression and one-way ANOVA analysis were used to carry out data analysis. The results of multiple regression analysis indicated that all the predictors have significant relationships with participation intentions except for firm motive. Based on the findings, hypermarket might choose to engage in CRM campaign that use “support local product” as a cause. By doing so, it might assist the hypermarket to differentiate themselves with other competitors in retail industry.